Structural and Electrical Properties of Nb3I8 Layered Crystal. Issue 3 (27th November 2018) - Kim, Bum Jun; Jeong, Byung Joo; Oh, Seungbae; Chae, Sudong; Choi, Kyung Hwan; Nanda, Sitansu Sekhar; Nasir, Tuqeer; Lee, Sang Hoon; Kim, Kwan‐Woo; Lim, Hyung Kyu; Chi, Linlin; Choi, Ik Jun; et al.
Abstract : Centimeter‐size single‐crystalline Nb3 I8, a new family of two‐dimensional materials, is first synthesized by a vapor transport reaction of niobium and iodine. Through the mechanical exfoliation method, the bulk Nb3 I8 crystal is cleaved to monolayer and multi‐layered flakes. It is confirmed to consist of numerous monolayers of Nb3 I8 bonded by weak van der Waals interaction. By utilizing atomic force microscopy (AFM) and scanning Kelvin probe microscopy (SKPM), the information on structure and electrical properties is obtained at the same time. The analysis results show that the surface potential difference and the work function tend to increase as the Nb3 I8 becomes thicker due to the interlayer screening effect. The results for the work function variation dependence on thickness are useful for selecting a suitable metal electrode for future Nb3 I8 ‐based nano‐devices which can have a significant impact on performance. Abstract : Centimeter‐size single‐crystalline Nb3I8 crystal, a new family of 2D materials, is firstly realized by a controlled solid‐state reaction of niobium and iodine. Since each layer of Nb3I8 is linked by a weak vdW forces, bulk Nb3I8 crystal is easily cleaved to monolayer and multi‐layered flakes by mechanical exfoliation. By utilizing the scanning Kelvin probe microscopy, the authors confirm that the surface potential difference and the work function tended to increase as the Nb3I8 become thicker due to the interlayer screening effect.